Analysis of the Competitiveness of Indonesia Shallot Commodity Exports in the International Market - Rizqi Muttaqin; Denny Saputera; Rizal Budi Santoso; Azzahra Putri Firmansyah; Rio Arsendo (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Despite significant growth in domestic production, Indonesia’s export performance remains relatively low and fluctuating compared to its production capacity. This study analyzes the competitiveness of Indonesian shallot exports in the international market during the period 2015-2024. This research employs a quantitative descriptive approach using key indicators, including Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Growth RCA, and Export Product Dynamics (EPD), to assess competitiveness and export dynamics. The results show that Indonesia’s RCA values are generally below one, indicating a lack of strong comparative advantage, while RSCA values remain negative, reflecting weak competitiveness relative to major competitors such as Thailand and India. Growth RCA analysis reveals unstable competitiveness trends, heavily influenced by external factors such as global prices, trade policies, and the COVID-19 pandemic. Furthermore, EPD analysis indicates that Indonesian shallot exports are frequently positioned in the “Lost Opportunity” and “Retreat” categories, suggesting an inability to capitalize on growing global demand. In contrast, competing countries consistently demonstrate stronger and more stable export performance. The study concludes that Indonesia’s high production potential has not been effectively translated into export competitiveness due to challenges related to product quality, logistics efficiency, and policy support. Therefore, strategic efforts are required to improve quality standards, enhance supply chain efficiency, and expand export markets in order to strengthen Indonesia’s position in the global shallot trade.